Сакрализация обыденности в рассказе Андрея Битова „Летучий голландец” - Radosz, Joanna (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2018)
The Flying Dutchman (Letuchiy Gollandets) from the collection Wheel (Koleso) belongs to the forgotten part of Andrei Bitov’s memoir-like prose. This short story stands as an epitaph for a Soviet speedway rider Gennadiy Vyunov. In his story, Bitov adds some sacred value to both speedway and the particular rider, until the sport becomes a supernatural phenomenon. The given article aims at analyzing the story and the means used to conduct the sacralization process on various levels: the plot, the language, the complex of intertextual relations, and therefore, presenting the unknown side of the well-known author of Pushkin House.